(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2014)
Background: School age is the active growing phase of childhood. It is a dynamic period of physical growth as well as of mental development of the child. Research indicates that health problems due to miserable nutritional status in primary school-age children are among the most common causes of low school enrolment, high absenteeism, early dropout and unsatisfactory classroom performance. Objective: The objective of this study was to assess the nutritional status among rural school children, in terms of the BMI, stunting and wasting among the children. Materials and methods: A descriptive type of cross-sectional study was conducted among the school children of two secondary schools located in Savar upazilla during January-March 2013. From these selected schools, a total number of 340 students aged 5-14 yrs were enrolled in the study. First face to face interview was conducted with available students with the help of purposive sampling technique. Then anthropometric measurement such as Age (in years), Heights (in cms), and Weight (in kgs) of each child were taken to assess their nutritional status. Results: The mean height of the children was (136.9; SD±8.57cm) not comparable with CDC 2000 (Centres for Disease Control and Prevention) standard. Among 340 students, 81.8% of the students were found to be under nourished. Underweight, stunting and wasting were present in 38.8%, 55.9%, and 25.9% of school children respectively. Underweight was associated with lower household wealth (p < .005). The mean weight (27.18 Kg; SD± 6.78 Kg) was lower than CDC 2000 standards. Among underweight children girls (50.3%) were found to be higher than boys (28.73%). The students were more stunted (55.9%) than wasted (25.9%). Only 10.29% of the students were found to be both wasted and stunted. Conclusion: The study revealed that high percentage of rural school children was malnourished. The study result also revealed the urgent need for initiation of school health programme with specific emphasis on, improvement of nutritional status, personal hygiene and prevention of diseases with the collaboration of governmental and non-governmental institutions. DOI: http://dx.doi.org/10.3329/bjpp.v30i1.20780 Bangladesh J Physiol Pharmacol 2014; 30(1):6-10